Public libraries in component cities social relevance of the San Pablo City Public Library - Ignacio, Gerald John D.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Public libraries are one of the oldest institutions that serve humanity. Through time, its function and definition has evolved in order to adapt to the ever changing needs of the society. From just being a primal repository of knowledge, it has become one of society's most important entities for the enhancement of the social fabric of a community.
This study is about the perception of social relevance of the stakeholders of the San Pablo City Public Library (SPCPL). The study sought to identify the demographics of the stakeholders of the library, and determine the perception on its capacity to meet the stated goals and its social relevance according to some social impact indicators. Finally, it compared the results gathered from this study with the perception of social relevance of the stakeholders of the Quezon City Public Library, a library situated in a highly urbanized area.
The tool used for the data gathering of the study is a structured questionnaire and the data gathered were interpreted via basic statistical concepts. The respondents were the stakeholders (identified and potential users) of the SPCPL.
The results show that most of the stakeholders of SPCPL are still unaware of the services that it offers to the general public. As such, its limited direct involvement to the community has resulted to a lot of undecided responses in different areas. The general perception from Almoniña and Paragua's study on Quezon City Public Library (QCPL) in 2012 are considerably better as compared to the perception of the stakeholders of the SPCPL.
It was noted that some of the branches of QCPL located in the less privileged areas generated similar results to that of SPCPL. Also, both institutions performed well in the areas which are stereotypically linked to a library, such as the provision of resosurces and providing support to education, as compared to those field specific services not typically related to the more well known services of a public library.
It was concluded that the public libraries of today are still being perceived as more of an institution which focuses its services to scholarly endeavor rather than one which caters to the everyday actual needs of the community. Also, it is clear that the social relevance of a public library is directly proportional to its effectivity and efficiency in the provision of its services, which in turn, is also directly propotional to its capability with respect to resources and facilities. As such, sufficient support should be provided in these institutions to reach its full potential as a true asset to the community.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Laguna -- Evaluation; Public libraries -- Philippines -- Laguna -- Use studies